2019
DOI: 10.1021/jacs.9b03007
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemiluminescence-Based Capacitance Microscopy for Label-Free Imaging of Antigens on the Cellular Plasma Membrane

Abstract: Electrochemiluminescence (ECL)-based capacitance microscopy using a square-wave voltage is established unprecedentedly to realize the label-free visualization of species on electrode surfaces and cellular plasma membranes. The drop in the local capacitance upon the binding of species to the surface or to a cellular membrane is derived to induce a relatively larger potential drop (V dl) across the double layer on the local electrode surface, which is utilized to prompt enhanced ECL at the binding position. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
131
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 187 publications
(142 citation statements)
references
References 35 publications
0
131
0
1
Order By: Relevance
“…It provides high ECL efficiency in heterogeneous as well as homogeneous formats and it is the most widely exploited ECL system to detect various biomolecules (e.g., proteins, peptides, ligands and oligonucleotides) and DNA, for immunological assays and ECL microscopy. [11][12][13][14][15][16][17][18][19][20][21][22] The heterogeneous ECL mechanism of the [Ru(bpy) 3 ] 2+ /TPrA system is an active area of investigation. 14,32,33,43,44 In such a conguration, the ECL luminophore is not free to diffuse and cannot be directly oxidised at the electrode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides high ECL efficiency in heterogeneous as well as homogeneous formats and it is the most widely exploited ECL system to detect various biomolecules (e.g., proteins, peptides, ligands and oligonucleotides) and DNA, for immunological assays and ECL microscopy. [11][12][13][14][15][16][17][18][19][20][21][22] The heterogeneous ECL mechanism of the [Ru(bpy) 3 ] 2+ /TPrA system is an active area of investigation. 14,32,33,43,44 In such a conguration, the ECL luminophore is not free to diffuse and cannot be directly oxidised at the electrode.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17] Different approaches have also been proposed to image cells by ECLM. 12,13,[18][19][20][21][22] Furthermore, the surface-conned emission allows ECLM to quantify different analytes simultaneously [23][24][25][26] as well as permitting high resolution visualization of nanomaterials such as nanoparticles and nanorods. [27][28][29][30][31] In ECL, the emission layer is typically conned in the near proximity of the electrode surface 32 and it is limited by the lifetime of the coreactant radicals (vide infra) and cannot be easily controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al reported the ECL-based capacitance microscopy for the first time. [68] In their work, a square wave voltage with high frequency was applied to the electrode while recording the ECL image. Upon the binding of nonconductive antibody (without ECL tags), the local capacitance decreases, which results in a higher potential drop across the double layer (V dl ) in these regions.…”
Section: Imaging Based Analysismentioning
confidence: 99%
“…As depicted in Figure 8a, cell-matrix adhesions are exactly in this space. Ru (bpy) 3 2 + generates bright emission at the bare surface, whereas cell-matrix adhesions function as inhibitors and steric exclusion [68] with permission from the American Chemical Society. sites of ECL reaction and thus appear as dark shadows under ECL microscopy.…”
Section: Imaging Based Analysismentioning
confidence: 99%
“…Plasma membrane (PM) systems have been extensively studied over several decades [1][2][3][4][5] on their association with proteins. Recent studies have shown that the role of proteins and their interactions with components of PM is extremely important to understand the mechanisms of protein anchoring into the membrane that can lead to oncogenesis [6].…”
Section: Introductionmentioning
confidence: 99%